20.7k views
2 votes
-3mn+4m-3 when m=2 and n=-4

User Born
by
5.6k points

2 Answers

3 votes

Answer:


\huge\boxed{29}

Solution Steps:

______________________________

1.) Fill in the variables with the information given:


  • -3(2)(-4)+4(2)-3

- M = 2

- N = -4

2.) Multiply:


  • -3 ×
    2=-6

  • 4 ×
    2=8

- The reason we multiply first is due to Order of Operations or PEMDAS: Parenthesis, Exponents, Multiplication, Division, Addition, Subtraction.

- When we see y(x) this just means whatever number or variable is before the parenthesis, you multiply it by that.

Equation at the end of Step 2:


  • -6(-4)+8-3

3.) Multiply again:


  • -6 ×
    -4=-24

- We do this once more because we had one last parenthesis.

Equation at the end of step 3:


  • 24+8-3

4.) Add:


  • 24+8=32

Equation at the end of Step 4:


  • 32-3

5.) Subtract:


  • 32-3=29

______________________________

User Poshanniraula
by
4.7k points
2 votes

Answer:

29

Explanation:

m = 2 and n = -4

-3mn + 4m - 3

-3(2)(-4) + 4(2) - 3

-6(-4) + 8 - 3

24 + 8 - 3

32 - 3 = 29

User Mark Avenius
by
5.7k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.